ALK-rearranged pulmonary adenocarcinoma in Thai Patients: From diagnosis to treatment efficacy. Issue 1 (December 2016) - Incharoen, Pimpin; Reungwetwattana, Thanyanan; Saowapa, Sakditad; Kamprerasart, Kaettipong; Pangpunyakulchai, Duangjai; Arsa, Lalida; Jinawath, Artit
Abstract Background Anaplastic lymphoma kinase (ALK ) gene rearrangement is detected in 3 % to 13 % of non-small cell lung carcinoma patients, and these patients benefit from ALK inhibitors. The aim of this study was to determine the prevalence, the clinical and histological characteristics and the treatment outcomes of ALK-rearranged lung adenocarcinoma using immunohistochemistry (IHC) IHC, reverse transcription polymerase chain reaction (RT-PCR) and fluorescence in situ hybridization (FISH) methodologies. Methods A total of 268 pulmonary adenocarcinoma patients were screened for ALK expression by ALK IHC, which was confirmed by FISH and/or RT-PCR for ALK gene rearrangement. The treatment outcomes of ALK-rearranged patients were retrospectively reviewed. Results ALK gene rearrangement was identified in 26 cases (9.7 %) with no EGFR co-mutation, and it showed significant associations with younger age, female sex and non-smoker status (p < 0.05). A cribriform growth pattern was identified as the dominant histologic feature, and a solid signet ring cell component was focally present in a minority of the cases. Among 12 ALK-rearranged patients with conventional treatment, seven cases in the early stage of disease were cured and alive, and five patients in the late stage of the disease progressed and died, with a median overall survival (OS) at 14 months. Of the 14 patients receiving crizotinib, all of them had clinical benefit from crizotinib treatment, with one patient having a complete response (CR), 12 patients having a partial response (PR) and one patient having stable disease (SD). On the cutoff date, six of 14 patients were continuing crizotinib treatment with a median time of response of 7.5 (3–13) months, while eight patients had disease progression, and five of them died with a median OS at 8 months. Conclusion ALK gene rearrangement tended to occur in younger, non-smoking, female patients. ALK IHC is a reliable screening method to detectALK gene rearrangement. Crizotinib therapy provided treatment benefit in ALK-rearranged adenocarcinoma patients especially in advanced stages of the disease.